2019
DOI: 10.1590/0034-7167-2017-0644
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Care for the transgender population: genders from the perspective of professional practice

Abstract: Objective: To describe and analyze the national and international scientific production on Nursing care for the transgender or gender-variance population. Method: Integrative review of the literature, conducted throughout the Virtual Health Library, Cumulative Index to Nursing and Allied Health Literature, Public Medline and Web of Science databases, without pre-established periods of time and using the descriptors "Transgender AND ‘Nursing Assistance'" and "Transgender AND ‘Nursing care'". Results: We inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 30 publications
0
23
0
4
Order By: Relevance
“…Despite the recognized advance in the production in the area, its various conceptual propositions, definitions, and theories can generate divergences and counterpoints in their application in specific settings and social groups. The application of these concepts, both in social groups and in the trans community, is a fundamental initiative for understanding the social dynamics of this vulnerable group, especially because they understand that the visibility or invisibility of the transgender person damages their identity and self-esteem, causing psychological distress that may lead to psychopathologies such as depression and anxiety, among others (9) . Therefore, understanding the social identity of the transgender person, especially in the field of health, provides interfaces to be discussed for the construction of an appropriate nursing practice for this group.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recognized advance in the production in the area, its various conceptual propositions, definitions, and theories can generate divergences and counterpoints in their application in specific settings and social groups. The application of these concepts, both in social groups and in the trans community, is a fundamental initiative for understanding the social dynamics of this vulnerable group, especially because they understand that the visibility or invisibility of the transgender person damages their identity and self-esteem, causing psychological distress that may lead to psychopathologies such as depression and anxiety, among others (9) . Therefore, understanding the social identity of the transgender person, especially in the field of health, provides interfaces to be discussed for the construction of an appropriate nursing practice for this group.…”
Section: Introductionmentioning
confidence: 99%
“…30 In a review study on the nursing care for the trans population 11 publications were found in the 2005-2001 period, most from abroad, with only one Brazilian publication. 31 The results show that few nurses feel able to serve this population and that there is lack of knowledge and competency for the interaction with trans people and for dealing with gender diversity in the professional practice; thus, it is necessary to increase or to include contents in the nursing curricula. 31 Corroborating with this data, a study with 19 students from a federal university in the Brazilian South Region evidenced weaknesses in their knowledge, both about their concepts of homo and bisexuality as well as about the training on the care for this group, with a superficial approach in classrooms, leading them to search for extracurricular activities.…”
Section: Nursing Lgbti+ Population and Primary Carementioning
confidence: 99%
“…31 The results show that few nurses feel able to serve this population and that there is lack of knowledge and competency for the interaction with trans people and for dealing with gender diversity in the professional practice; thus, it is necessary to increase or to include contents in the nursing curricula. 31 Corroborating with this data, a study with 19 students from a federal university in the Brazilian South Region evidenced weaknesses in their knowledge, both about their concepts of homo and bisexuality as well as about the training on the care for this group, with a superficial approach in classrooms, leading them to search for extracurricular activities. 32 Homo and bisexual women have fewer chances of being offered to undergo a cytopathological cervical examination and are exposed to acts of violence during the procedure, such as the use of a speculum of an inadequate size and without the necessary lubrication.…”
Section: Nursing Lgbti+ Population and Primary Carementioning
confidence: 99%
“…Podemos perceber a necessidade da criação de espaços onde a enfermagem possa estar presente na construção de projetos terapêuticos para a população trans e na criação de vínculos, estabelecendo assim a confiança tão necessária para o acolhimento nos serviços de saúde (Rosa et al, 2019).…”
Section: Categoria 1 -Expectativas Objetivasunclassified